From Spark to Flame. On Writing "I See Fire" - Bjarki Dagur Svanþórsson 1990- (2014)
This final assignment is a result of a lifelong desire to write fiction and a passion for telling stories. The assignment consists of a novella, I See Fire (roughly 38,000 words) and a report on the writing process (about 5,500 words). I See Fire is a thriller centered around Michael McMorrow, a former detective with the New York Police Department. Events from his past have left him deeply troubled, and he moves to Iceland with his wife, a native of the country, in order to attain closure and move on with his life. Mere months after their relocation, however, Michael‘s wife is killed in a tragic car accident. A stranger in a country where he does not belong, Michael loses himself in a pit of grief and substance abuse, until the disappearance of a young girl forces him back from the brink. During his search for the missing teen, Michael is forced to confront his own dark deeds, the truth about his wife‘s death, and the things that lurk beneath the surface of Iceland itself. The report details the genesis of the novella, its story and characters, as well as explaining the various trials that arose during the writing and editing processes. The various sources of inspiration for the story are presented, and the methods I used to create characters in whom readers will, hopefully, be able to emotionally invest. In order for the reader to understand the report fully, I suggest reading the novella, in its entirety, before moving on to the essay. The report is divided into five primary chapters, each focusing on a different aspect of the creative process. Plotting, character creation, setting and dialogue are all discussed in detail, as well as the research that secured the foundation that the story rests upon.